2010
DOI: 10.1364/oe.18.004986
|View full text |Cite
|
Sign up to set email alerts
|

CMOS-integrated high-speed MSM germanium waveguide photodetector

Abstract: A compact waveguide-integrated Germanium-on-insulator (GOI) photodetector with 10 +/- 2fF capacitance and operating at 40Gbps is demonstrated. Monolithic integration of thin single-crystalline Ge into front-end CMOS stack was achieved by rapid melt growth during source-drain implant activation anneal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
124
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(130 citation statements)
references
References 19 publications
5
124
0
1
Order By: Relevance
“…These properties make Ge one of the most promising materials for CMOS compatible photonic components including near-infra-red photodetectors [1][2][3][4] and, possibly, lasers [5][6][7] in the important spectral region of 1.3-1.6 lm. However, it is well known that conventional Ge heteroepitaxy on Si is complicated by the 4.2% difference in Ge and Si lattice constants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make Ge one of the most promising materials for CMOS compatible photonic components including near-infra-red photodetectors [1][2][3][4] and, possibly, lasers [5][6][7] in the important spectral region of 1.3-1.6 lm. However, it is well known that conventional Ge heteroepitaxy on Si is complicated by the 4.2% difference in Ge and Si lattice constants.…”
Section: Introductionmentioning
confidence: 99%
“…Kamins, 2 X. Wu, 3 Detailed studies of the structural and optical properties of axial silicon-germanium nanowire heterojunctions show that despite the 4.2% lattice mismatch between Si and Ge they can be grown without a significant density of structural defects. The lattice mismatch induced strain is partially relieved due to spontaneous SiGe intermixing at the heterointerface during growth and lateral expansion of the Ge segment of the nanowire.…”
mentioning
confidence: 99%
“…Among possible semiconductor material choices for Si-based photonics, Ge is also the most promising candidate for active photonic devices on Si, thanks to its pseudo-direct gap electronic structure and compatibility with CMOS fabrication processes. Micrometer-scale-thick Ge-on-Si photonics, such as waveguide-coupled photodetectors (Liu et al, 2006;Assefa et al, 2010;Wang et al, 2011;Going et al, 2015;Sorianello et al, 2015), electro-absorption modulators (Chaisakul et al, 2012;Feng et al, 2012;Ren et al, 2012), and light sources (Liu et al, 2010(Liu et al, , 2012Camacho-Aguilera et al, 2012) have demonstrated their effectiveness and functionality. However, given their micrometer scales, these Ge/Si heterostructures are too thick to be directly integrated with the prevailing submicron or even nanometer-scale-thick Si electronic devices.…”
Section: Ge-based Mos Gate-stack Engineeringmentioning
confidence: 99%
“…Here, threading dislocation densities have been reduced to the range of ~10 7 /cm 2 . Among them are, the graded buffer layer with chemical mechanical polishing (CMP) approach [27], the two step growth method [28], and the rapid melting growth method [29]. The two step low-temperature buffer layer growth is often employed due to no requirement for thick buffer layers, capability of growing thick epi layers, and compatibility with the back end of line (BEOL) CMOS processing.…”
Section: Modified Two-step Growthmentioning
confidence: 99%